Improve Science Process Skills and Learning Outcomes with The Quantum Learning Model - Wiyoko, Tri; Aprizan, Aprizan; Riska, Riska; Wulandari, Titis (UIN Fatmawati Sukarno Bengkulu, 2021)
Learning in elementary schools that has not been optimal in involving students actively will have a negativeimpact on science process skills and learning outcomes. Students will be actively involved in learning if theapplied learning model involves students to experience the learning process as a whole. This research is aClassroom Action Research (CAR) which is carried out in two cycles.. Retrieval of data using theobservation sheet and learning outcome test questions. The results obtained indicate that the learningprocess with Quantum Learning can improve the science process skills of students. Increasing scienceprocess skills on average obtains very good criteria. The improved science process skills include; 1)Formulating Problems, 2) Formulating hypotheses, 3) Observing, 4) Collecting data, 5) concluding, 6)Communicating. Furthermore, the learning outcomes obtained by students using the Quantum Learningmodel can increase learning outcomes from cycle I by 73.68%, increasing to 89.47% in Cycle II. So theQuantum Learning learning model can improve the process skills and learning outcomes of students ingrade V Elementary School